3D bioprinting and the current applications in tissue engineering. Issue 8 (4th July 2017) - Huang, Ying; Zhang, Xiao‐Fei; Gao, Guifang; Yonezawa, Tomo; Cui, Xiaofeng
Abstract: Bioprinting as an enabling technology for tissue engineering possesses the promises to fabricate highly mimicked tissue or organs with digital control. As one of the biofabrication approaches, bioprinting has the advantages of high throughput and precise control of both scaffold and cells. Therefore, this technology is not only ideal for translational medicine but also for basic research applications. Bioprinting has already been widely applied to construct functional tissues such as vasculature, muscle, cartilage, and bone. In this review, the authors introduce the most popular techniques currently applied in bioprinting, as well as the various bioprinting processes. In addition, the composition of bioink including scaffolds and cells are described. Furthermore, the most current applications in organ and tissue bioprinting are introduced. The authors also discuss the challenges we are currently facing and the great potential of bioprinting. This technology has the capacity not only in complex tissue structure fabrication based on the converted medical images, but also as an efficient tool for drug discovery and preclinical testing. One of the most promising future advances of bioprinting is to develop a standard medical device with the capacity of treating patients directly on the repairing site, which requires the development of automation and robotic technology, as well as our further understanding of biomaterials and stem cell biology to integrate various printing mechanisms for multi‐phasic tissue engineering. Abstract : Bioprinting as an enabling technology for tissue engineering possesses the promises of fabricating highly mimicked tissue or organs with digital control. Here we present the bioprinting techniques in our aspect of review and the current successful applications in tissue engineering.